The Epistemic Stress Equation: A Necessary Quadratic Law of Imbalance - Sungwan Boksuwan (Zenodo (CERN European Organization for Nuclear Research), 2026)
This record provides a timestamped version of the manuscript"The Epistemic Stress Equation: A Necessary Quadratic Law of Imbalance." The paper establishes a necessary quadratic relation between imbalanceand an invariant scalar quantity in epistemic systems, under minimalstructural conditions. This upload serves as an initial public record of the result.
Keywords: Mathematical and Theoretical Analysis; Heat Transfer and Numerical Methods; Elasticity and Wave Propagation